The fatty acid amide hydrolase inhibitor URB597 exerts anti-inflammatory effects in hippocampus of aged rats and restores an age-related deficit in long-term potentiation. - LYNCH, MARINA ANNETTA; MURPHY, NIAMH; GOWRAN, AOIFE; CAMPBELL, VERONICA ANN (My University, 2012)
Background: Several factors contribute to the deterioration in synaptic plasticity which accompanies age and one of these is neuroinflammation. This is characterized by increased microglial activation associated with increased production of proinflammatory cytokines like interleukin-1 ? (IL-1 ? ). In aged rats these neuroinflammatory changes are associated with a decreased ability of animals to sustain long-term potentiation (LTP) in the dentate gyrus. Importantly, treatment of aged rats with agents which possess anti-inflammatory properties to decrease microglial activation, improves LTP. It is known that endocannabinoids, such as anandamide (AEA), have anti-inflammatory properties and therefore have the potential to decrease the age-related microglial activation. However, endocannabinoids are extremely labile and are hydrolyzed quickly after production. Here we investigated the possibility that inhibiting the degradation of endocannabinoids with the fatty acid amide hydrolase (FAAH) inhibitor, URB597, could ameliorate age-related increases in microglial activation and the associated decrease in LTP. Methods: Young and aged rats received subcutaneous injections of the FAAH inhibitor URB597 every second day and controls which received subcutaneous injections of 30% DMSO-saline every second day for 28 days. Long-term potentiation was recorded on day 28 and the animals were sacrificed. Brain tissue was analyzed for markers of microglial activation by PCR and for levels of endocannabinoids by liquid chromatography coupled to tandem mass spectrometry. Results: The data indicate that expression of markers of microglial activation, MHCII, and CD68 mRNA, were increased in the hippocampus of aged, compared with young, rats and that these changes were associated with increased expression of the proinflammatory cytokines interleukin (IL)-1 ? and tumor necrosis factor- ? (TNF ? ) which were attenuated by treatment with URB597. Coupled with these changes, we observed an age-related decrease in LTP in the dentate gyrus which was partially restored in URB597-treated aged rats. The data suggest that enhancement of levels of endocannabinoids in the brain by URB597 has beneficial effects on synaptic function, perhaps by modulating microglial activation
PUBLISHED
Keywords: Age, Long-term potentiation (LTP), Endocannabinoids, Anandamide microglial activation, Hippocampus, Fatty acid amide hydrolase (FAAH); Age, Long-term potentiation (LTP), Endocannabinoids, Anandamide microglial activation, Hippocampus, Fatty acid amide hydrolase (FAAH)